2012
DOI: 10.1136/jmedgenet-2012-101203
|View full text |Cite|
|
Sign up to set email alerts
|

A 600 kb deletion syndrome at 16p11.2 leads to energy imbalance and neuropsychiatric disorders

Abstract: BackgroundThe recurrent ∼600 kb 16p11.2 BP4-BP5 deletion is among the most frequent known genetic aetiologies of autism spectrum disorder (ASD) and related neurodevelopmental disorders.ObjectiveTo define the medical, neuropsychological, and behavioural phenotypes in carriers of this deletion.MethodsWe collected clinical data on 285 deletion carriers and performed detailed evaluations on 72 carriers and 68 intrafamilial non-carrier controls.ResultsWhen compared to intrafamilial controls, full scale intelligence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
320
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 273 publications
(349 citation statements)
references
References 53 publications
27
320
1
1
Order By: Relevance
“…It is confirmed that a region of chromosome 16p11.2 influences susceptibility to autism when either deleted or duplicated [14]. Furthermore, a 600 kb deletion at 16p11.2 leads to a group of neuropsychiatric disorders [21]. 16p11.2 encompasses twenty-five genes, which spans 500 kb and is flanked by 147 kb low copy repeats that are 99% identical [20].…”
Section: Introductionmentioning
confidence: 70%
“…It is confirmed that a region of chromosome 16p11.2 influences susceptibility to autism when either deleted or duplicated [14]. Furthermore, a 600 kb deletion at 16p11.2 leads to a group of neuropsychiatric disorders [21]. 16p11.2 encompasses twenty-five genes, which spans 500 kb and is flanked by 147 kb low copy repeats that are 99% identical [20].…”
Section: Introductionmentioning
confidence: 70%
“…2,4,6,7,9,15,17 As shown by 4C-seq, FISH, and Hi-C, the two 16p11.2 CNV-prone regions are reciprocally engaged in evolutionary-conserved complex chromatin looping, as well as coordinated expression of encompassed genes. 17,45 Here we assessed whether these findings were paralleled by genetic interactions between the 28 and 9 single-copy genes within the 16p11.2 600 kb BP4-BP5 and 220 kb BP2-BP3 intervals, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5]9,10 The two CNVs have also been shown to interact at the chromatin level, by 4C, FISH, Hi-C, and concomitant expression changes. 17,45 To investigate whether the two regions are also conducive to genetic interactions, we co-injected LAT, the driver of the HC phenotype of the BP2-BP3 CNVs, with mRNAs encoding KCTD13, the driver of the HC phenotype of the BP4-BP5 CNVs, and MAPK3 or MVP, modifiers of the same BP4-BP5 HC phenotype, and we evaluated the number of proliferating cells.…”
Section: A B C D E F H Gmentioning
confidence: 99%
See 2 more Smart Citations